Inpatient satisfaction: an analysis of Malaysian public hospitals - Abd. Manaf, Noor Hazilah (Emerald, 2012)
Purpose - The objective of this study is to provide an empirical analysis on inpatient satisfaction in Malaysian public hospitals.